2021
DOI: 10.3390/genes12091421
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing of Corallococcus sp. Strain EGB Reveals the Genetic Determinants Linking Taxonomy and Predatory Behavior

Abstract: Corallococcus sp. strain EGB is a Gram-negative myxobacteria isolated from saline soil, and has considerable potential for the biocontrol of phytopathogenic fungi. However, the detailed mechanisms related to development and predatory behavior are unclear. To obtain a comprehensive overview of genetic features, the genome of strain EGB was sequenced, annotated, and compared with 10 other Corallococcus species. The strain EGB genome was assembled as a single circular chromosome of 9.4 Mb with 7916 coding genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Whole-genome phylogeny was performed to confirm the taxonomic classification. Based on the clustering results of orthologous proteins, we randomly selected 135 single-copy genes that conserved in all nine species (Edgar, 2004 ; Zhao et al, 2021 ). Alignments of the concatenated sequences of 135 single-copy genes were generated by the Muscle algorithm, and then, the phylogenetic tree was constructed by the neighbor joining algorithm with 1,000 bootstrap replicates in MEGA11 (Kumar et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Whole-genome phylogeny was performed to confirm the taxonomic classification. Based on the clustering results of orthologous proteins, we randomly selected 135 single-copy genes that conserved in all nine species (Edgar, 2004 ; Zhao et al, 2021 ). Alignments of the concatenated sequences of 135 single-copy genes were generated by the Muscle algorithm, and then, the phylogenetic tree was constructed by the neighbor joining algorithm with 1,000 bootstrap replicates in MEGA11 (Kumar et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Comparative genome analysis of candidate biocontrol agent Corallococcus sp. strain EGB revealed that abundant extracellular chitinases, β-(1,3)-glucanases, and proteases are likely involved in the predation of phytopathogenic fungi ( Zhou et al, 2019 ; Zhao et al, 2021 ). Investigation of myxobacterial response to prey quorum signals revealed that oxidative degradation of toxic alkyl quinolones produced by P. aeruginosa benefits myxobacterium Cystobacter ferrugineus predation of the opportunistic pathogen ( Akbar et al, 2022 ; Figure 1A ).…”
Section: Absence Of General Genetic Indicators For Predatory Performancementioning
confidence: 99%
“…Biyoteknolojik gelişmeler kültür olarak elde edilmesinin zor olduğu ya da hiç elde edilemeyeceği düşünülen mikroorganizmaların geleceğine umut olmuştur. Bunlardan biri de miksobakterilerdir [6] ve sahip oldukları genomik özelliklerinden dolayı ikincil metabolit üretimi açısından çok önemli bir grup olduğu görülmektedir [7][8][9].…”
unclassified